'I feel lost and somehow messy': a narrative inquiry into the identity struggle of a first-year university student. Issue 6 (19th September 2021) - Ding, Feng; Curtis, Fiona
ABSTRACT: The transition to university life is challenging, involving academic adaptation and social and lifestyle adjustment, so it is no surprise that attrition is at its highest in the first year of attending university. Studies have investigated factors influencing students' adjustment, and the formation of a new learner identity within university has proven to be crucial. However, few studies have provided rich qualitative longitudinal data to illustrate identity formation in the first year of university. Adopting a narrative inquiry approach, this paper tells the story of Christy, a mainland Chinese student attending a university in Hong Kong, who struggled in her first year. With data collected from in-depth interviews, the participant's journal entries and email correspondence, this narrative inquiry illustrates the development of Christy's identity as a university student.